Trade Policy: Home Market Effect vs Terms of Trade Externality - Alessia Campolmi; Harald Fadinger; Chiara Forlatiz (FIW - Research Centre International Economics, 2009)
We study trade policy in a two-sector Krugman type model of trade. We conduct a general analysis allowing for three different instruments: tariffs, export taxes and production subsidies. For each instrument we consider unilateral trade policy without retaliation. When carefully disentangling the different effects that determine policy makers' choices and modeling general equilibrium effects of taxes/tariffs, we find that production subsidies are always inefficiently low and driven by terms of trade effects. In the cases of tariffs and export taxes the home market effect prevails for some parameter combinations but mostly trade policy is determined by terms of trade effects and the desire to reduce distortions arising from monopolistic competition. Hence, our analysis sheds new light on trade policy in a model of intra-industry trade.
Keywords: F12; F13; F42; 330; Home Market Effect; Terms of Trade; Tariffs and Subsidies